The Literary Oeuvre of Peter Svetina in the Selection for the Večernica Award - Bednjički Rošer, Barbara (Trideset let literarne nagrade večernica, 2026)
This paper examines Peter Svetina’s nominated and award-winning works for the Večernica Award during the award period from 1997 to 2025. The analysis includes all nine nominated works, among them three award-winning titles: Ropotarna (2013), Kako zorijo ježevci (2016), and Molitvice s stopnic (2017). The discussion focuses on the thematic, motivational, and genre characteristics of the selected corpus, as well as on distinctive features of Svetina’s poetics, such as humor, nonsense, lyricism, and linguistic playfulness. Attention is also paid to the diversity of literary forms and representations of childhood in the works under consideration. The paper aims to demonstrate that Peter Svetina’s nominated and award-winning works make a significant contribution to contemporary Slovenian children’s and young adult literature and to the prominence of the Večernica Award.